Fear no man : Don James, the '91 Huskies, and the seven-year quest for a national football championship - Gastineau, Mike (University of Washington Press, 2021)
"This is the story of perhaps the greatest University of Washington Husky football team ever-and arguably, one of the top college football teams of all time. The 1991 Huskies, helmed by legendary coach Don James, chalked up a 12-0 record and won the Rose Bowl. They outscored opponents by an average of 31 points per game and the team included no less than 25 future NFL players. Alongside the Miami Hurricanes, the Huskies were recognized as national cochampions. How did a team built on contradictions-with an old-school coach, noted for his traditional approach, and a team of notably rambunctious players-make it work? Drawing on dozens of new interviews with athletes, coaching staff, and more, Seattle sports journalist Mike Gastineau tells a lively story of the unexpected twists of an epic season. Packed with never-before-told stories, his research offers new insider perspectives on iconic plays, outsized personalities, and an unusual set of team dynamics that led to one perfect season"--